Exploring Character Dynamics: Unveiling Dominant Values in Physics Education - Sulaiman, Marlita; Yetti Latifah; Deneri, Yasemin; Gonzales, Jomar R. (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: This research aims to determine the character values ​​that are more dominant among teachers in students, with a focus on eliminating values ​​such as integrity, honesty, discipline, caring and responsibility in the context of learning at school. Methodology: This research uses mixed methods with quantitative and qualitative descriptive approaches. The population is all physics teachers at Darul Ulum Private Madrasah Aliyah, with a sample of three teachers selected purposively. Research instruments include questionnaires and interviews, with data analysis using partial analysis for quantitative and the Miles and Huberman model for qualitative. Main Findings: The results of the research show that of the three character values ​​studied, the one that appears more dominant in students is the discipline character value of 88.89%, where students always follow and carry out the rules set by the school, then the responsibility character value is 86%, In students there is still a high value of responsibility for what is a burden and looking after goods or whatever is their responsibility. Finally, the honest character value was 84.75%, a character value that was lower than the character value studied. Novelty/Originality of this study: This research highlights the determination of dominant character values ​​in students, especially in discipline, responsibility and honesty in learning physics. With a sample of three physics teachers, this research uses quantitative descriptive methods and partial data analysis to reveal a new understanding of student character in the context of learning at school.